Análise do impacto da gestão sustentável da cadeia de suprimentos no desempenho inovador - Klimeck, Kalien Alves (2015)
The traditional way of business faces different criticisms and emerges demand for sustainable practices. Sustainable development emerges as a premise for the longevity of the business. To meet external pressures in respect of sustainability and get it more extensively, companies were involved sustainability in their supply chain and not just in the organization. Innovation is also a growing demand for organizations mainly visa their connection to sustainability. The mining sector is often considered obsolete for not offering innovative products and perform extractive activities that can result in environmental and social degradation. Thus, this study aims to analyze the influence of sustainable supply chain management in innovative performance of companies in the Brazilian mining sector. To answer it carried out a descriptive study with a quantitative approach with companies in the Brazilian mining sector associated with Brazilian Mining Institute - IBRAM. Sustainable supply chain management was measured based on the practices identified by Pagell and Wu (2009). And the innovative performance was identified by process innovation scales proposed by Makkonen and Van Der Have (2013) and Gunday et al. (2011), and process innovation capabilities scale proposed by Camisón and Villar-Lopes (2014). In brief, the research results indicate that companies in the mining sector has a high agreement with the scales used, indicating the existence of sustainable practices in the supply chain and innovation performance. Also indicate the existence of significant positive association between sustainable supply chain management and innovation performance. Using the moderating variables, it is observed that both the position in the supply chain as the business size affect the way that occur relationships between factors. Indicating that business characteristics influence the way these relate to sustainability and innovation.